Anti-CdtB and anti-vinculin antibodies to diagnose irritable bowel syndrome in inflammatory bowel disease patients - Luisa Leite Barros; Gabriela Leite; Walter Morales; Gillian M. Barlow; Matheus Freitas Cardoso de Azevedo; Alexandre de Sousa Carlos; Adérson Omar Mourão Cintra Damião; Mark Pimentel; Alberto Queiroz Farias (BMC Gastroenterology)
Abstract Background Despite adequate treatment, a subgroup of patients with inflammatory bowel disease (IBD), including Crohn`s disease and ulcerative colitis, have persistent gastrointestinal symptoms that are not always related to mucosal damage. Recently, two autoantibodies, anti-CdtB and anti-vinculin, were validated as post-infectious IBS (PI-IBS) markers, however there is limited evidence of its diagnostic role in IBD population. Methods Patients with more than 3 bowel movements/day and indication of colonoscopy were enrolled. Samples were collected at the time of colonoscopy for assessment of serum levels of anti-CdtB and anti-vinculin antibodies. Results A total of 160 subjects were included in 4 groups: active IBD (n = 44); quiescent IBD and chronic diarrhea IBD-IBS (n = 25); predominant-diarrhea IBS (n = 45) and controls (n = 46). The mean value of the optical density for anti-CdtB was 1.2 ± 0.65 in group 1, 1.27 ± 0.64 in group 2, 1.49 ± 0.47 in the group 3 and 1.6 ± 0.68 in group 4, p = 0.012. For anti-vinculin, optical densities were: 1.34 ± 0.78 in group 1, 1.46 ± 0.92 in group 2, 1.31 ± 0.79 in group 3 and 1.41 ± 0.86 for controls (p = 0.875). Using a cut-off of 1.56 for anti-CdtB, the positivity between groups was n = 10 (22.7%) in group 1, n = 9 (34.6%) in group 2, 19 (43.2%) in group 3, 21 (45.7%) in group 4 (p = 0.106). The positivity of anti-vinculin using a cut-off of 1.6 was n = 18 (40.9%) in group 1, n = 11 (42.3%), n = 15 (34.1%), n = 22 (47.8%) (p = 0.622). Conclusions Our findings show that anti-CdtB and anti-vinculin could not identify IBD-IBS patients or discriminate IBS-D from healthy controls.